POSTFEMINISM CONCEPT IN LUX INDONESIA “LUX BERANI CANTIK 30” ADVERTISEMENT: A MULTIMODAL CRITICAL DISCOURSE ANALYSIS - Hanifah, Owyana Nur; Kurniawan, Muhammad Hafiz; Farida, Hana; Atmantika, Zanuwar Hakim (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2023)
Advertisement does not only promote products but also conveys a message behind the promotion. One of the current trending concepts is femvertising. The initial purpose of femvertising is to fill the concept of advertising that uses pro-female talent, words, and images to empower women and girls. As a result, advertising has attracted more consumers and evolved into a movement aimed at selling more items to women rather than a genuine subversion and changing gender stereotypes. Lux is also one of the brands indicated to use the advertising concept, as in its advertisement